Countering the myths: Lesbians write about the men in their lives - Elwin, Rosamund (Women's Press, 1996)
When false ideas prescribe our existence, our lives are limited, our communities are diminished, and we are, sadly, set against one another. In Countering the Myths, lesbians write about fathers, brothers, lovers, friends, co-workers, strangers. Their words are cautious, tender, urgent, angry. They dispute entrenched myths and provoke, instead, difficult questions. Their stories and poems provide an opportunity to unite in an exciting and liberating lesbian sexuality and life.
Keywords: approches et analyses; droits des femmes*; lesbianisme; personnes lesbiennes; ressource en ligne; sexualité; thématiques

Getting wet: Tales of lesbian seductions - Allain, Carol; Elwin, Rosamund (Women's Press, 1992)
This is sex fiction that gets under the covers and rolls them back, sex fiction that inscribes lesbian erotics poignantly, playfully and powerfully.
Keywords: 1900-1999; amériques; approches et analyses; canada; corps; lesbianisme; périodes historiques; ressource en ligne; régions géographiques; sexualité; thématiques; érotisme